Adjuvant therapies in advanced hepatocellular carcinoma: moving forward from the STORM - Bouattour, Mohamed (Trials, 2016)
ABSTRACT: Like other previous treatments and approaches, sorafenib, an antiangiogenic drug, failed to show any benefit in the adjuvant setting for hepatocellular carcinoma in a large clinical trial. We discuss reasons and implications of these negative results and the implications for clinical practice and future research. TRIAL REGISTRATION: ClinicalTrials.gov: NCT00692770. Registered 5 June 2008. This study has been completed.